Aspectos clínico-sociais relacionados ao tabagismo em idosos assistidos pelo Programa de Saúde da Família - Kumpel, Cláudia (2005)
Introdution -The process of aging and it s natural consequence the oldness, is concerns of the humanity since the beginning the civilization, as the Geriatry and the Gerontology they are relatively new scientific areas, the idea is transparent that the concern with the oldness has origin in the current days. Between the aged tobacconists are very frequent illness and generally his associate to other illnesses. The social aspects to the tobacconist still very little studied by the scientific community. Hypotheses this study had been that the social discrimination to the tobacconist occurs mainly in public environments and how much will be the time of tobacconist will be greater degree of dependence to the nicotine. Objectives To evaluate the degree of dependence of the nicotine in the aged tobacconists, to investigate the knowledge of the aged about possible illness caused for the consumption of the tobacco; to inquire if someone already received social discrimination for to be tobacconist; to investigate the factors that had contributed so that the aged to became him a smoking. Methods had been interviewed 80 tobacconists individuals taken care of by the program of health of the family in the Capão Redondo in São Paulo, all had answered two questionnaires, one to evaluate the degree of dependence to the nicotine the other on related social aspects to the tobacconist. Results had completed this study 76 patients, the age measured was 64,5 years, smoke history had been 44,3 years, the great source of income familiar has origin in the social providence, the bigger factors of risk that contribute for the beginning of the tobacconist had been; parents, and friends that are smoking, OR 1,6 and 1,7 respectively. The illness related tobacco more known for the interviewed was the cancer, illness bigger prevalence it was systemic arterial hypertension. The smoke history was one better marker of than bigger number of illnesses between the age this study p = 0,036. The social discrimination to the tobacconist in 73,3% of the cases was made by family. Conclusion The biggest social discrimination received by the tobacconists it was in the proper family; parents, friends, spouses smoking and curiosity are factors that influence other individuals positively to become smoking; it does not have relation between tabagica history and degree of dependence to the nicotine. the risk to smoking individual to have a related illness tobacco is 4,4 times bigger of than didn t have illness